Tissue characterization of uterine fibroids with an intravoxel incoherent motion model: The need for T2 correction. Issue 4 (5th March 2018) - Qu, Feifei; Hor, Pei‐Herng; Fischer, John; Muthupillai, Raja
Abstract : Background: Diminished signal intensity of uterine fibroids in T2 ‐weighted images is routinely used as a qualitative marker of fibroid hypoperfusion. However, quantitative classification of fibroid perfusion with intravoxel incoherent motion (IVIM) model‐based metrics is not yet clinically accepted. Purpose: To investigate the influence of T2 correction on the estimation of IVIM model parameters for characterizing uterine fibroid tissue. Study Type: Prospective. Population: Fourteen women with 41 fibroids (12 Type I and 29 Type II, per Funaki classification) underwent diffusion‐weighted imaging and T2 mapping. Field Strength: Diffusion‐weighted images ( b values: 0, 20, 40, 60, 100, 200, 400, 600, 800, 1000 s/mm 2 ) and T2 maps were obtained at 1.5T. Assessment: The effect of uterine fibroid T2 variation on IVIM model parameters (diffusion coefficient, perfusion coefficient, and perfusion volume fraction) were numerically modeled and experimentally evaluated without ( D, D*, f ) and with ( Dc, D c *, fc ) T2 correction. The relationship of T2 with D and the T2 ‐corrected perfusion volume fraction ( f c ) was also examined. Statistical Test: D‐ values and f‐ values estimated with and without T2 correction were compared by using a two‐tailed Student's t ‐test. Results: Type II fibroids had higher D and f than Type I fibroids, but the differences were not significant (Type I vs. Type II, D : 0.83 ± 0.20 vs. 0.80 ± 0.25 mm 2 /s, P = 0.78; f : 23.64 ± 4.87% vs. 25.27 ± 7.46%, P = 0.49). For Type I and Type II fibroids, f c was lower than f, and f c of Type II fibroids was significantly higher than that of Type I fibroids (Type I vs. Type II, f c : 7.80 ± 1.88% vs. 11.82 ± 4.13%, P = 0.003). Both D and f c exponentially increased with the increase of fibroid T2 as functions: D c ( T 2 ) = − 1.52 × 10 − 3 ⋅ e − 3.42 T 2 290 + 1.84 × 10 − 3 and f c ( T 2 ) = − 0.2336 ⋅ e − 3.217 T 2 290 + 0.2269, respectively. D asymptotically approached 1.79 × 10 −3 mm 2 /s, and f c approached 21.74%. Data Conclusion: T2 correction is important when using IVIM‐based models to characterize uterine fibroid tissue. Level of Evidence : 2 Technical Efficacy : Stage 1 J. Magn. Reson. Imaging 2018;48:994–1001.